Experimental study on the characteristic and function of oxide film formed on grinding wheel in ELID precision grinding. Issue 5 (10th October 2019) - Zhang, Jia-Bo; Yang, Yang; Zhang, Xiao-Hui; Guan, Jia-Liang; Zheng, Li-Yan; Li, Guang
Abstract : Purpose: The purpose of this study is to investigate the characteristic and function of oxide film formed on grinding wheel in electrolytic in-process dressing (ELID) precision grinding and improve the quality of ELID grinding. Design/methodology/approach: Dynamic film forming experiments were carried out with a simulation device close to the actual processing conditions. Then, the ELID grinding experiments of bearing rings were performed using grinding wheels with good film forming effect. The experiment was designed by quadratic regression general rotation combination method. The influence of grinding depth, electrolytic voltage, duty cycle and grinding wheel linear speed on grinding effect is analyzed. Findings: A mathematical model for the formation rate of oxide film was established. The experiments show that the composition of grinding wheel and grinding fluid, as well as the electrical parameters, influence the film forming effect. Thus, the oxide film plays an important role in ELID grinding. Originality/value: This study provides a reference for the design and selection of grinding wheel and grinding fluid and the setting of process parameters in ELID grinding.